2006
DOI: 10.1084/jem.20060155
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of airway hyperresponsiveness by induction of airway mucosal CD4+CD25+ regulatory T cells

Abstract: An important feature of atopic asthma is the T cell–driven late phase reaction involving transient bronchoconstriction followed by development of airways hyperresponsiveness (AHR). Using a unique rat asthma model we recently showed that the onset and duration of the aeroallergen-induced airway mucosal T cell activation response in sensitized rats is determined by the kinetics of functional maturation of resident airway mucosal dendritic cells (AMDCs) mediated by cognate interactions with CD4+ T helper memory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
166
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(176 citation statements)
references
References 35 publications
8
166
1
1
Order By: Relevance
“…It is of interest that the proportion of Tregs in the skin increases with age and can contribute to reduced immune responses observed in elderly individuals (18). Although we were not able to examine this, other human tissues, such as gut and lung, also reportedly contain significant numbers of Tregs (45,46). From the available, data it appears that Tregs in these peripheral tissues also display a memory phenotype (31,32,47).…”
Section: Cd45ramentioning
confidence: 85%
“…It is of interest that the proportion of Tregs in the skin increases with age and can contribute to reduced immune responses observed in elderly individuals (18). Although we were not able to examine this, other human tissues, such as gut and lung, also reportedly contain significant numbers of Tregs (45,46). From the available, data it appears that Tregs in these peripheral tissues also display a memory phenotype (31,32,47).…”
Section: Cd45ramentioning
confidence: 85%
“…CD4ϩCD25ϩFoxp3ϩ Tregs generally represent 5-15% of the total CD4ϩ population in a mouse, and CD4 depletion will eliminate these cells as well. A study in OVAsensitized rats revealed that CD25ϩ ␣␤T cells in the tracheal mucosa begin to increase after the first intranasal challenge of OVA and remained elevated after 10 daily challenges (36). These cells were able to suppress OVA-specific T cell proliferation ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Kearley et al (2005) (Strickland et al, 2006). A major strength of this study was the use of a sensitive and highly accurate technique for determination of airway mechanics separately in the airways and tissue parenchyma (LFOT).…”
Section: Regulatory T Cells and Airways Hyperresponsiveness Attenuationmentioning
confidence: 99%
“…Naturally occurring Treg cells were traditionally described to be thymically-derived with the function of maintaining systemic homeostasis to control total lymphocyte numbers in order to protect the integrity of tissues and organs in vivo (Sakaguchi et al, 2001). More recently, Treg populations have been induced in vitro and in vivo via culturing with cytokines or in mouse models via pathogenic or allergenic stimulation (Verhasselt et al, 2004;Kretschmer et al, 2005;Luo et al, 2005;Skapenko et al, 2005;Moo-Young et al, 2006;Nicolson & Wraith, 2006;Strickland et al, 2006). The induced Treg populations also have the ability to control other lymphocytes in vivo however they differ from naturally occurring Treg in a number of ways which will be discussed below.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
See 1 more Smart Citation